2022
DOI: 10.1002/anie.202203650
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Regio‐ and Enantioselective Protonation for the Synthesis of Chiral Allenes: Synergistic Effect of the Counterion and Water

Abstract: A highly enantioselective tandem Pudovik addition/[1,2]‐phospha‐Brook rearrangement of α‐alkynylketoamides with diarylphosphine oxides was achieved with a N,N′‐dioxide/ScIII complex as the catalyst. This protocol features broad substrate scope, high regio‐ and enantioselectivity, and good functional‐group compatibility, providing a straightforward route to various trisubstituted allenes with a diarylphosphinate functionality in good yields with high enantioselectivities (up to 97 % yield, 96 % ee). Control exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Very recently, we developed a Lewis acid-catalyzed enantioselective γ-protonation of α-alkynylketoamides and diarylphosphine oxides with the assistance of water (Scheme c), confirming that chiral N , N ′-dioxide/metal complexes are efficient catalysts to enable [1,2]-phospha-Brook rearrangement. Inspired by this work, we envisaged the possibility of an asymmetric multicomponent reaction of ketone and phosphite with a suitable Michael acceptor catalyzed by chiral Lewis acid.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Very recently, we developed a Lewis acid-catalyzed enantioselective γ-protonation of α-alkynylketoamides and diarylphosphine oxides with the assistance of water (Scheme c), confirming that chiral N , N ′-dioxide/metal complexes are efficient catalysts to enable [1,2]-phospha-Brook rearrangement. Inspired by this work, we envisaged the possibility of an asymmetric multicomponent reaction of ketone and phosphite with a suitable Michael acceptor catalyzed by chiral Lewis acid.…”
mentioning
confidence: 78%
“…Terada's group accomplished the multicomponent S N Ar reaction utilizing [1,2]-phospha-Brook rearrangement, and an enantioselective example between isatin, silylated secondary phosphite, and electron-deficient fluoroarene was tested with the use of chiral iminophosphorane as well, affording the 3-aryl-3-hydroxy oxindole with 65% yield and 88% ee (Scheme 1b). 3e Very recently, we developed a Lewis acid-catalyzed enantioselective γ-protonation of α-alkynylketoamides and diarylphosphine oxides with the assistance of water (Scheme 1c), 5 confirming that chiral N,N′-dioxide/metal complexes 6 are efficient catalysts to enable [1,2]-phospha-Brook rearrangement. Inspired by this work, we envisaged the possibility of an asymmetric multicomponent reaction of ketone and phosphite with a suitable Michael acceptor 7 catalyzed by chiral Lewis acid.…”
mentioning
confidence: 80%
“…38 Most recently, the use of this rearrangement has also been reported in the preparation of (difluoromethyl)cycloalkenes, 39 the Passerini–Smiles reaction of α-ketophosphonates, 40 and the asymmetric synthesis of enantioenriched axial chiral allenes. 41 All of the above mentioned reactions proceed under basic conditions, and examples of a Lewis acid catalyzed reaction are extremely rare. 42 To our knowledge, the Brønsted acid catalyzed [1,4]-phospha-Brook rearrangements observed in this study, for the conversion of organocatalyst 14b into the phosphonamidate 15 , has not been previously reported.…”
Section: Table 1 Asymmetric Transfer Hydrogenation Of Q...mentioning
confidence: 99%
“…Generally, in such situations, trace H 2 O can play two roles: it can donate and accept protons, facilitating proton transfer [71][72][73] and it can form hydrogen bonds with reactants in a cocatalytic reaction. 74,75 Here, the two models were separately tested by carrying out DFT calculations, and the results showed that the trace H 2 O co-catalyzed the reaction with the acid. It occurred in the addition step (Fig.…”
Section: Of Esi †mentioning
confidence: 99%